The Role of Islamic Boarding School Education in Character Formation (Perspective of Islamic Psychology) - Adama Sheriff Jallow (Al Misykat : Journal of Islamic Psychology, 2023)
Islamic boarding school is a traditional school that focuses on Islamic education and is usually founded by a kyai or cleric. At the Islamic boarding school, students study Islam, Arabic, interpretation of the Qur'an, hadith, jurisprudence, morals, and various other sciences. In this study, researchers used literature research methods. A literature research method is an approach used to collect and analyze information from published related sources, such as journals, books, reports, and other documents. The aim is to obtain an overview of the topic under study and obtain the required information. In this research, we will discuss further: Islamic values in character building, the role of Islamic boarding school education in character building, and the role of Islamic boarding school education in character building (Islamic psychology perspective)